Reactive oxygen species-activated Ca/calmodulin kinase IIδ Is required for late INa augmentation leading to cellular Na and Ca overload - Wagner, Stefan; Ruff, Hanna M.; Weber, Sarah L.; Bellmann, Sarah; Sowa, Thomas; Schulte, Timo; Anderson, Mark E.; Grandi, Eleonora; Bers, Donald M.; Backs, Johannes; Belardinelli, Luiz; Maier, Lars S. (Circulation research, 2011)
Rationale: - In heart failure Ca/calmodulin kinase (CaMK)II expression and reactive oxygen species (ROS) are increased. Both ROS and CaMKII can increase late INa leading to intracellular Na accumulation and arrhythmias. It has been shown that ROS can activate CaMKII via oxidation. - - Objective: - We tested whether CaMKIIδ is required for ROS-dependent late INa regulation and whether ROS-induced Ca released from the sarcoplasmic reticulum (SR) is involved. - - Methods and Results: - 40 μmol/L H2O2 significantly increased CaMKII oxidation and autophosphorylation in permeabilized rabbit cardiomyocytes. Without free [Ca]i (5 mmol/L BAPTA/1 mmol/L Br2-BAPTA) or after SR depletion (caffeine 10 mmol/L, thapsigargin 5 μmol/L), the H2O2-dependent CaMKII oxidation and autophosphorylation was abolished. H2O2 significantly increased SR Ca spark frequency (confocal microscopy) but reduced SR Ca load. In wild-type (WT) mouse myocytes, H2O2 increased late INa (whole cell patch-clamp). This increase was abolished in CaMKIIδ−/− myocytes. H2O2-induced [Na]i and [Ca]i accumulation (SBFI [sodium-binding benzofuran isophthalate] and Indo-1 epifluorescence) was significantly slowed in CaMKIIδ−/− myocytes (versus WT). CaMKIIδ−/− myocytes developed significantly less H2O2-induced arrhythmias and were more resistant to hypercontracture. Opposite results (increased late INa, [Na]i and [Ca]i accumulation) were obtained by overexpression of CaMKIIδ in rabbit myocytes (adenoviral gene transfer) reversible with CaMKII inhibition (10 μmol/L KN93 or 0.1 μmol/L AIP [autocamtide 2-related inhibitory peptide]). - Conclusions: - Free [Ca]i and a functional SR are required for ROS activation of CaMKII. ROS-activated CaMKIIδ enhances late INa, which may lead to cellular Na and Ca overload. This may be of relevance in hear failure, where enhanced ROS production meets increased CaMKII expression.
Im Text ist "Na" tiefgestellt
Gesehen am 29.11.2022